The Decision of Dismissal, Suspension, or Discontinuation of Employment of Public/Private School Teachers - Jui-Che Wu (National Taipei University of Education, 2014)
There have been controversies over the legal attribute of the decision of dismissal, suspension, or discontinuation of employment of public and private school teachers. The Supreme Administrative Court passed a resolution in July, 2009. In this resolution, the legal relationship between public schools and their teachers was regarded as administrative contracts while the legal attribute of the decision of dismissal, suspension, or discontinuation of employment was categorized into administrative dispositions. Besides, the administrative disposition will not take effect until it obtains approval from the competent educational authorities, and teachers can seek administrative appeal as remedy first, which makes remedy procedure complicated. Therefore, this study first attempts to categorize the legal relationship between the public and private schools and their teachers. Then, the legal attribute of the decision of dismissal, suspension, or discontinuation of employment and the remedy procedure are discussed. It is concluded in this study that the legal relationships between public/private schools and their teachers fall into the categories of administrative/civic contract respectively. Any decision of dismissal, suspension, or discontinuation of employment should be based on this categorization, and the remedy procedure can thus be reduced. Besides teacher's appeal and re-appeal system being in accordance with Teacher's Act, the appeal of declaratory judgment on contractual relationship to either the Administrative Court or the Civic Court can also be filed. As a result, the remedy procedure can be simplified to an extent to follow the basic principles stated in the resolution.